Recombinant erythropoietin in clinical practice. Issue 933 (1st July 2003) - Ng, T; Marx, G; Littlewood, T; Macdougall, I
Abstract : The introduction of recombinant human erythropoietin (RHuEPO) has revolutionised the treatment of patients with anaemia of chronic renal disease. Clinical studies have demonstrated that RHuEPO is also useful in various non-uraemic conditions including haematological and oncological disorders, prematurity, HIV infection, and perioperative therapies. Besides highlighting both the historical and functional aspects of RHuEPO, this review discusses the applications of RHuEPO in clinical practice and the potential problems of RHuEPO treatment.